Biodiesel production from ceiba pentandra oil using enzymatic reaction / Norjannah Basan - Norjannah, Basan (2017)
Biodiesel is a type of renewable fuel and a potential alternative for continuously consumed fossil resources. Despite the fact that biodiesel productions commonly use chemical-catalyzed reaction due to its easy steps and high yield, enzymatic transesterification is also able to generate high biodiesel yield with an even greener approach: no chemical involve (except methanol as its substrate), no saponification, and no wastewater generation. Nonetheless, there are some problems associated with enzymatic reaction: high cost of lipase enzyme and its deactivation. In this research, a commercial enzyme, Candida Antarctica lipase immobilized on acrylic resin (Novozym 435) was used to convert non-edible oil from tropical resources, Ceiba pentandra (kapok) to biodiesel using methanol as acyl acceptor. C. pentandra oil was obtained from its seeds that were usually thrown away after the cotton had been collected. Tests on methanol concentration, stepwise addition, and enzyme pretreatment were conducted to improve enzyme activity. Optimization process (using artificial neural network based program and genetic algorithm) and enzyme reusability test were performed as an effort to reduce the total biodiesel production cost. The results obtained showed that high methanol concentration would cause enzyme deactivation and this could be prevented by maintaining each addition of methanol to about 1 molar equivalent per step. Furthermore, biodiesel yield increased when using t-butanol but decreased when using sodium chloride solution as enzyme pretreatment. Optimization process demonstrated that the optimum condition was at 57.42 °C temperature, 3:1 methanol to oil molar ratio, and 71.89 h reaction time to produce a biodiesel yield of 80.75%. The reusability of enzyme was measured at 63.69% relative yield after three batches. The calculated biodiesel production costs were at $15.69/L and $0.97/L for enzyme price at $800/kg (current enzyme cost) and $8/kg (enzyme cost in the future) respectively. To conclude, biodiesel production from Ceiba pentandra oil using biocatalyst is feasible and can be further improved for industrialization. Keywords: Ceiba pentandra, enzyme, biodiesel, stepwise addition, optimization